2002
DOI: 10.1086/340787
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Comparison of DNA Sequences between Humans and Chimpanzees

Abstract: A total of 8,859 DNA sequences encompassing approximately 1.9 million base pairs of the chimpanzee genome were sequenced and compared to corresponding human DNA sequences. Although the average sequence difference is low (1.24%), the extent of changes is markedly different among sites and types of substitutions. Whereas approximately 15% of all CpG sites have experienced changes between humans and chimpanzees, owing to a 23-fold excess of transitions and a 7-fold excess of transversions, substitutions at other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
211
4
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(253 citation statements)
references
References 26 publications
37
211
4
1
Order By: Relevance
“…In contrast, only 0.82% of ancestrally TpG or CpA show a change to CpG. This roughly estimated ∼sevenfold difference in forward and reverse mutation rates is in agreement with previous studies on disease mutations and comparative sequence analysis, which have shown CpG mutations to be 5-20 times more frequent than other types of point mutations (Batzer et al 1990;Yang et al 1996;Krawczak et al 1998;Giannelli et al 1999;Ebersberger et al 2002).…”
Section: Directionality Of the Cpg Mutationssupporting
confidence: 91%
“…In contrast, only 0.82% of ancestrally TpG or CpA show a change to CpG. This roughly estimated ∼sevenfold difference in forward and reverse mutation rates is in agreement with previous studies on disease mutations and comparative sequence analysis, which have shown CpG mutations to be 5-20 times more frequent than other types of point mutations (Batzer et al 1990;Yang et al 1996;Krawczak et al 1998;Giannelli et al 1999;Ebersberger et al 2002).…”
Section: Directionality Of the Cpg Mutationssupporting
confidence: 91%
“…Similar trends have also been observed for HSA21q based on smaller comparisons with the chimpanzee genome 18 .…”
Section: Base Substitutionssupporting
confidence: 82%
“…Sequence divergence between human and chimpanzee is relatively low for CYP3A43 and CYP3A7 (0.88 and 1%, respectively), as well as for CYP3A4 and CYP3A5 (0.86 and 0.66%) compared to the genome-wide average of 1.24%. 22 We identified a total of 224 polymorphic sites, including 13 biallelic and three multiallelic indels. Two hundred and four polymorphic sites were located in noncoding sequence and 20 in coding sequence, including eight synonymous (s) and 11 ns substitutions.…”
Section: Re-sequencing Survey Design and Resultsmentioning
confidence: 99%